Malignant extracutaneous melanomas - Mate, Miguel; Borges, J Freddy; D'Auria, Agustín; Priario, Julio C (Cirugía del Uruguay, 1981)
Having treated a series of 19 cases of malignant extracutaneous melanomas, the authors review epidemiolcgy, anatomopathol'ogy and ciinics of this co·ndition.